Spanish Cultural Adaptation and Inter-Rater Reliability of the Revised Knox Preschool Play Scale - Sergio Serrada-Tejeda; Marta Pérez-de-Heredia-Torres; Susan H. Knox; Patricia Sánchez-Herrera-Baeza; Rosa M. Martínez-Piédrola; Paula Obeso-Benítez; Sergio Santos-del-Riego (Children, 2023)
Background: The Revised Knox Preschool Play Scale (RKPPS) is a comprehensive assessment test that observes the level of play development; however, there is no culturally adapted version available with stable psychometric values that would allow its widespread use and provide objective information during clinical evaluations. Methods: Cross-cultural adaptation included direct and retrospective translations, along with cognitive interviews with pediatric occupational therapists to analyze the comprehensibility of the translation. In addition, a final phase of linguistic revision was carried out to determine the grammatical and semantic fit of the adapted version. Finally, inter-rater reliability was analyzed in a sample of typically developing children aged four to six years old. Results: The processes of translation and back-translation, cognitive interview, and linguistic review determined an adequate grammatical and semantic equivalence to the Spanish cultural context. Almost perfect agreement, with values between 0.82 and 0.94, was obtained for items and play dimensions, indicating that the precision of the measurements between both evaluators was excellent. Conclusions: The cross-culturally adapted version of the RKPPS meets the necessary adjustments for the sociocultural context and can be used in the clinical practice of occupational therapy.